2010
DOI: 10.1158/0008-5472.can-09-4598
|View full text |Cite|
|
Sign up to set email alerts
|

Gemcitabine Sensitivity Can Be Induced in Pancreatic Cancer Cells through Modulation of miR-200 and miR-21 Expression by Curcumin or Its Analogue CDF

Abstract: Curcumin induces cancer cell growth arrest and apoptosis in vitro, but its poor bioavailability in vivo limits its antitumor efficacy. We have previously evaluated the bioavailability of novel analogues of curcumin compared with curcumin, and we found that the analogue CDF exhibited greater systemic and pancreatic tissue bioavailability. In this study, we evaluated the effects of CDF or curcumin alone or in combination with gemcitabine on cell viability and apoptosis in gemcitabine-sensitive and gemcitabine-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
372
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 404 publications
(393 citation statements)
references
References 46 publications
16
372
0
5
Order By: Relevance
“…The miR-200 family (miR-200a, miR-200b, miR-200c, miR-141, and miR-429) is a cluster of miRNA that are highly correlated with epithelial-mesenchymal transition, with miR-200b being identified as a critical regulator of tumor invasion, metastasis, and chemosensitivity (Feng et al, 2012). The miR-200 family is associated with the acquisition of epithelial-to-mesenchymal transition and gemcitabine sensitivity in pancreatic adenocarcinoma (Li et al, 2009;Ali et al, 2010;Bao et al, 2011). Previous studies have reported the close association of EFNB2 with the development of gastric cancer, neuroblastomas, esophageal squamous cell carcinoma, and other tumors (Tang et al, 1999(Tang et al, , 2000Kataoka et al, 2002;Tachibana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-200 family (miR-200a, miR-200b, miR-200c, miR-141, and miR-429) is a cluster of miRNA that are highly correlated with epithelial-mesenchymal transition, with miR-200b being identified as a critical regulator of tumor invasion, metastasis, and chemosensitivity (Feng et al, 2012). The miR-200 family is associated with the acquisition of epithelial-to-mesenchymal transition and gemcitabine sensitivity in pancreatic adenocarcinoma (Li et al, 2009;Ali et al, 2010;Bao et al, 2011). Previous studies have reported the close association of EFNB2 with the development of gastric cancer, neuroblastomas, esophageal squamous cell carcinoma, and other tumors (Tang et al, 1999(Tang et al, , 2000Kataoka et al, 2002;Tachibana et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also demonstrated that miR-21 modulates the chemosensitivity of cancer cells primarily by targeting PTEN or PDCD4 (Moriyama et al, 2009;Ali et al, 2010;Giovannetti et al, 2010;Tomimaru et al, 2010). In addition, cancer tissue miR-21 has been shown to be a biomarker for chemoresistance and clinical outcome following adjuvant therapy in resectable pancreatic cancer (Hwang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[102][103][104] Several publications have shown that inhibition of oncogenic miRNAs such as miRNA-21 or reactivation of tumor suppressive miRNAs such as miRNA-34 can sensitize PC cells to gemcitabine chemotherapy. [76][77][78][79][80][81] These results suggest that specific targeting of miRNAs by a variety of approaches could open new avenues for PC treatment by overcoming drug resistance and thus improving PCoutcome. [105][106][107][108] Conclusions Overall, these results are highly encouraging and outline various starting points for new treatment strategies.…”
Section: Micrornas As Epigenetic Targetsmentioning
confidence: 97%
“…78 , which may in turn result in the reversal of EMT phenotype, led to the sensitizing of gemcitabine-resistant PC cells to gemcitabine. 79 Li et al presented that the expression of miRNA-200b, miRNA-200c, let-7b, let-7c, let-7d and let-7e was significantly downregulated in gemcitabine-resistant cells, which showed EMT characteristics such as elongated fibroblastoid morphology, lower expression of epithelial marker E-cadherin and higher expression of mesenchymal markers such as vimentin and ZEB1. Moreover, the reexpression of miRNA-200 by transfection studies or treatment of gemcitabine-resistant cells with either DIM or isoflavone resulted in the downregulation of ZEB1, Slug and vimentin, which was consistent with morphologic reversal of EMT phenotype leading to epithelial morphology.…”
Section: Micrornas As Epigenetic Targetsmentioning
confidence: 99%